Getting the ecology into interactions between plants and the plant growth-promoting bacterium Pseudomonas fluorescens - Hol, W. H. Gera; Bezemer, T. Martijn; Biere, Arjen (Frontiers in Plant Science, 2013)
Plant growth-promoting rhizobacteria (PGPR) are increasingly appreciated for their contributions to primary productivity through promotion of growth and triggering of induced systemic resistance in plants. Here we focus on the beneficial effects of one particular species of PGPR (Pseudomonas fluorescens) on plants through induced plant defence. This model organism has provided much understanding of the underlying molecular mechanisms of PGPR-induced plant defence. However, this knowledge can only be appreciated at full value once we know to what extent these mechanisms also occur under more realistic, species-diverse conditions as are occurring in the plant rhizosphere. To provide the necessary ecological context, we review the literature to compare the effect of P. fluorescens on induced plant defence when it is present as a single species or in combination with other soil dwelling species. Specifically, we discuss combinations with other plant mutualists (bacterial or fungal), plant pathogens (bacterial or fungal), bacterivores (nematode or protozoa) and decomposers. Synergistic interactions between P. fluorescens and other plant mutualists are much more commonly reported than antagonistic interactions. Recent developments have enabled screenings of P. fluorescens genomes for defence traits and this could help with selection of strains with likely positive interactions on biocontrol. However, studies that examine the effects of multiple herbivores, pathogens, or herbivores and pathogens together on the effectiveness of PGPR to induce plant defences are underrepresented and we are not aware of any study that has examined interactions between P. fluorescens and bacterivores or decomposers. As co-occurring soil organisms can enhance but also reduce the effectiveness of PGPR, a better understanding of the biotic factors modulating P. fluorescens -plant interactions will improve the effectiveness of introducing P. fluorescens to enhance plant production and defence.